2015
DOI: 10.1002/jca.21393
|View full text |Cite
|
Sign up to set email alerts
|

Use of a dual lumen port for automated red cell exchange in adults with sickle cell disease

Abstract: Red cell exchange (RCE) is a common procedure in adults with sickle cell disease (SCD). Implantable dual lumen Vortex (DLV) ports can be used for RCE in patients with poor peripheral venous access. We performed a retrospective cohort study of RCE procedures performed in adults with SCD. The main objective of the study was to compare the inlet speed, duration of procedures and rate of complications performed through DLV ports to those performed through temporary central venous and peripheral catheters. Twenty-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 11 publications
1
37
1
Order By: Relevance
“…Implantable ports are a well‐tolerated, long‐term option in patients expected to undergo regular exchanges because of a reduced care burden on the patient and infection rate (up to 10x less than central venous catheters) due to their subcutaneous placement . However, previous studies have reported an increased complication rate and decreased flow rates in comparison to temporary central venous catheters …”
Section: Introductionmentioning
confidence: 99%
“…Implantable ports are a well‐tolerated, long‐term option in patients expected to undergo regular exchanges because of a reduced care burden on the patient and infection rate (up to 10x less than central venous catheters) due to their subcutaneous placement . However, previous studies have reported an increased complication rate and decreased flow rates in comparison to temporary central venous catheters …”
Section: Introductionmentioning
confidence: 99%
“…These include access via a peripheral vein, temporary central venous catheter (CVC) access (via subclavian, jugular or femoral veins), placement of indwelling double‐lumen ports (e.g. Vortex), or the creation of arteriovenous fistulas . A broad consensus is that, where possible, a peripherally placed device should be the first choice for elective therapeutic apheresis procedures (TAs).…”
Section: Introductionmentioning
confidence: 99%
“…Of the other 24 studies, 14 were single-armed studies that reported absolute or ‘before and after data’, with seven published as full peer-reviewed studies [2430] and seven as conference abstracts [31–37]. Two were single-armed studies on manual exchange, both published as conference abstracts [38, 39].…”
Section: Review Of Clinical Effectiveness Evidencementioning
confidence: 99%
“…The EAC focussed on results from the six comparative studies with manual RBC exchange [18–23] because these provided the most useful data relevant to the decision problem, and the peer-reviewed single-armed studies of the Spectra Optia [28] and Cobe Spectra systems [24, 26, 27, 29, 30], as these studies were fully reported and provided useful supporting data. Details of these studies are summarised in Table 1.…”
Section: Review Of Clinical Effectiveness Evidencementioning
confidence: 99%
See 1 more Smart Citation